On Ruwet’s semiotically oriented theory of music - Krupińska, Eliza (Interdisciplinary Studies in Musicology, 2018)
The article deals with Nicolas Ruwet’s semiotically oriented theory of music, which constitutes the canvas of his taxonomic analysis. Ruwet adopts from Jakobson’s semiotic structuralism the binary model of the sign, together with its key concepts of equivalence and introversive semiosis. Structural understanding of art began with the poetic function of language distinguished by Jakobson, which is defined as the projection of the principle of equivalence from the axis of selection to the axis of combination. The principle of equivalence, regarded by Ruwet as the regulating principle of musical syntax was, in Jakobson’s view, the answer to the question about what kind of semiosis was involved in music. The latter, described by Jakobson as introversive, deserves attention not only in view of its association with taxonomic analysis, but also because of its conceptual convergence with Leonard B. Meyer’s theory of meaning and formal iconisms of David Osmond-Smith.